Child health and maternal health knowledge: evidence from Vietnam - Tuyen Thi Mong Nguyen; Quyen Le Hoang Thuy To Nguyen; Phong Thanh Nguyen (Intelektual Pustaka Media Utama, 2022)
The care and protection of children are vital because children are the future of the country. Their health links to the development of adult human capital and the national economy. Informal maternal education is the major driver of child health but has never been formalized. This paper investigates the effects of maternal health knowledge on child health using a survey of 200 households in Ho Chi Minh City, Vietnam. The theory of household production has been applied to create a child health model. Anthropometric indicators of weight-for-age and height-for-age are set as the proxies for child health. The models are regressed separately for the weight-for-age and height-for-age Z-scores of children under five. The research results showed that the number of years of maternal schooling does have a positive impact on child anthropometric outcomes but its effects are crowded out by maternal health gained from the mother’s access to health information through pubic media and genetic inheritance, but these are inferior to environmental factors such as housing, sanitation, and health knowledge. The findings confirm that Vietnam can improve the status of child care and protection can be improved even under the constraints of limited access to maternal formal education).